RENAL DENERVATION IN CKD PATIENTS: PATHOPHYSIOLOGICAL RATIONALE, CLINICAL EVIDENCE, AND CONTEMPORARY PERSPECTIVES - Sidhi Laksono; Wella Widyani (Fakultas Kedokteran Universitas Alkhairaat, 2026)
ABSTRACT Hypertension is a central driver of cardiovascular morbidity and progressive renal dysfunction in patients with chronic kidney disease (CKD), yet optimal blood pressure control remains challenging, particularly in advanced disease stages. Resistant hypertension is common in CKD, reflecting complex interactions among volume overload, neurohormonal activation, sympathetic overactivity, and vascular dysfunction. This narrative review synthesizes contemporary evidence on the pathophysiological mechanisms underlying hypertension in CKD, diagnostic challenges related to blood pressure assessment, and integrated therapeutic strategies. Particular emphasis is placed on the evolving role of device-based interventions, especially renal denervation, as an adjunctive therapy for carefully selected patients with resistant hypertension. We review current data supporting renal denervation, discuss patient selection considerations, and highlight unresolved questions regarding long-term efficacy and safety in CKD populations. Special clinical contexts, including dialysis, kidney transplantation, and older adults, are addressed, along with common misconceptions that contribute to therapeutic inertia. By integrating mechanistic insights with emerging clinical evidence, this review aims to inform a more individualized, patient-centered approach to hypertension management in CKD and to clarify the potential clinical niche of renal denervation within contemporary treatment paradigms. ABSTRAK Hipertensi merupakan pendorong utama morbiditas kardiovaskular dan disfungsi ginjal progresif pada pasien dengan penyakit ginjal kronis (CKD), namun kontrol tekanan darah yang optimal masih menjadi tantangan, terutama pada stadium penyakit yang lebih lanjut. Hipertensi resisten sering ditemukan pada CKD, mencerminkan interaksi kompleks antara kelebihan volume, aktivasi neurohormonal, peningkatan aktivitas simpatis, dan disfungsi vaskular. Tinjauan naratif ini mensintesis bukti terkini mengenai mekanisme patofisiologis yang mendasari hipertensi pada CKD, tantangan diagnostik terkait penilaian tekanan darah, serta strategi terapi terintegrasi. Penekanan khusus diberikan pada peran intervensi berbasis perangkat yang terus berkembang, terutama denervasi ginjal, sebagai terapi tambahan pada pasien terpilih dengan hipertensi resisten. Kami meninjau data terkini yang mendukung denervasi ginjal, membahas pertimbangan seleksi pasien, serta menyoroti pertanyaan yang belum terjawab terkait efektivitas dan keamanan jangka panjang pada populasi CKD. Konteks klinis khusus, termasuk dialisis, transplantasi ginjal, dan populasi usia lanjut, juga dibahas, bersama dengan kesalahpahaman umum yang berkontribusi terhadap inersia terapeutik. Dengan mengintegrasikan wawasan mekanistik dan bukti klinis yang berkembang, tinjauan ini bertujuan untuk mendukung pendekatan manajemen hipertensi pada CKD yang lebih individual dan berpusat pada pasien, serta memperjelas potensi posisi klinis denervasi ginjal dalam paradigma terapi kontemporer.